2017
DOI: 10.1002/jrs.5112
|View full text |Cite
|
Sign up to set email alerts
|

In‐situRaman study of phengite compressed in water medium under simultaneously highP–Tparameters

Abstract: The in‐situ method of Raman spectroscopy was used to study the layered mineral phengite, K(Al,Mg)2(Si,Al)4O10(OH)2, compressed in water under simultaneously high temperatures and pressures (respectively, up to 373 °С and 12.5 GPa). The implemented conditions were typical of modeling the ‘cold’ subduction zones in lithospheric slabs. The high pressures and temperatures were produced in an electrically heated diamond‐anvil cell. Measured Raman spectra have demonstrated a high Р–Т stability of the mineral. No non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Furthermore, we studied its vibrational response to compression up to 42 GPa at ambient T in diamond anvil cell (DAC) experiments. These data are compared with recent studies on the devolatilisation of natural phengite containing trace amounts of NH + 4 (Liu et al, 2019;Yang et al, 2017) and with our own experimental results as well as with existing data (Goryainov et al, 2017;Zhang et al, 2010) on the dehydration of synthetic and natural ammonium-free phengite. NH 4 -endmember phengite is not reported from natural rocks so far.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, we studied its vibrational response to compression up to 42 GPa at ambient T in diamond anvil cell (DAC) experiments. These data are compared with recent studies on the devolatilisation of natural phengite containing trace amounts of NH + 4 (Liu et al, 2019;Yang et al, 2017) and with our own experimental results as well as with existing data (Goryainov et al, 2017;Zhang et al, 2010) on the dehydration of synthetic and natural ammonium-free phengite. NH 4 -endmember phengite is not reported from natural rocks so far.…”
Section: Introductionmentioning
confidence: 75%
“…The lattice modes of phengite have been assigned by means of IR and Raman spectroscopy (e.g. Goryainov et al, 2017;McKeown et al, 1999). In addition to the lattice modes, other vibrational modes in NH 4 -phengite come from the NH + 4 molecule located at the interlayer cation site, as well as from the OH situated in the octahedral layer (OH stretching vibration).…”
Section: Ambient Ftir Spectroscopymentioning
confidence: 99%
“…Goryainov et al carried out an in‐situ Raman study of phengite compressed in water medium under simultaneously high P–T parameters. The high pressures and temperatures were produced in an electric heated diamond anvil cell, and the measured Raman spectra demonstrated a high P–T stability of the mineral . Guo et al reported a comparative investigation of the vibrational properties of bulk 2H ‐MoS 2 and its exfoliated nanosheets under high pressure.…”
Section: High Pressure and Temperature Studiesmentioning
confidence: 99%
“…The high pressures and temperatures were produced in an electric heated diamond anvil cell, and the measured Raman spectra demonstrated a high P-T stability of the mineral. [204] Guo et al reported a comparative investigation of the vibrational properties of bulk 2H-MoS 2 and its exfoliated nanosheets under high pressure. The systematic research about the 2LA (M) in bulk 2H-MoS 2 suggests that the high-pressure behavior of this double resonance Raman mode arises from the pressure-induced metalization and band gap closure.…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%
“…Petrov calibrated the peak positions, half widths, and peak intensities of methane Raman bands with the goal of using this calibration to accurately determine the pressure of methane‐containing media. Behavior of phengitic mica at high‐pressure and ‐temperature conditions, typical for “cold” subduction zone, was analyzed by Goryainov et al. The pressure dependence of Raman bands for alkaline carbonate (nyerereite) was obtained by Rashchenko et al in order to estimate residual pressure values for melt inclusions in olivine from sheared garnet peridotites, one of the deepest mantle xenoliths.…”
Section: Raman Spectroscopy and Extreme Conditionsmentioning
confidence: 99%